2021
DOI: 10.2147/jhc.s300680
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sarcopenia on Two-Year Mortality in Patients with HCV-Associated Hepatocellular Carcinoma After Radiofrequency Ablation

Abstract: Purpose Radiofrequency ablation (RFA) appears effective for the treatment of hepatocellular carcinoma (HCC). Evaluation of prognostic factors is imperative for patient selection and improving treatment efficacy. This study aimed to assess sarcopenia as a predictor of the outcome of RFA in patients with HCC. Methods This prospective study included all patients with HCC on top of HCV-related cirrhosis who underwent RFA and followed up for a minimum of two years. CT scan w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Regarding the research design, 38 studies were designed as retrospective studies, and four studies were conducted prospectively. Twenty-two studies were included from Japan ( 14 , 22 42 ), six from Korea ( 16 , 43 47 ), four from China ( 48 51 ), two from Egypt ( 52 , 53 ), two from Germany ( 15 , 54 ), two from Italy ( 55 , 56 ), one each from Netherlands, Canada, United States of America (USA), and France ( 57 60 ). HCC patients were treated by hepatectomy, sorafenib, lenvatinib, TACE, yttrium-90 radioembolization, RFA, or the combination of these.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the research design, 38 studies were designed as retrospective studies, and four studies were conducted prospectively. Twenty-two studies were included from Japan ( 14 , 22 42 ), six from Korea ( 16 , 43 47 ), four from China ( 48 51 ), two from Egypt ( 52 , 53 ), two from Germany ( 15 , 54 ), two from Italy ( 55 , 56 ), one each from Netherlands, Canada, United States of America (USA), and France ( 57 60 ). HCC patients were treated by hepatectomy, sorafenib, lenvatinib, TACE, yttrium-90 radioembolization, RFA, or the combination of these.…”
Section: Resultsmentioning
confidence: 99%
“…SMI is the most widely used index and sarcopenia is defined as SMI < 42 cm 2 /m 2 for men and <38 cm 2 /m 2 for women based on the guideline proposed by Japan Society of Hepatology (JSH) ( 61 ). Among twenty-seven studies using SMI, eight studies used the cut-points proposed by JSH ( 14 , 22 , 32 , 35 , 42 , 45 , 49 , 52 ), six studies employed the Martin cut-points ( 41 , 53 , 55 , 57 , 58 , 60 ), four studies applied the Vledder cut-points ( 27 , 28 , 34 , 38 ), and their own cut-points were measured in other studies. HR was estimated by univariate and multivariate Cox proportional hazards regression to investigate the influence of sarcopenia on OS and/or PFS of HCC patients in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…There are yet no studies investigating the influence of sarcopenia for breast cancer patients undergoing locoregional therapies. For RFA, several studies showed that low pre-treatment PMI and SMI were associated with lower OS in HCC patients after RFA [55][56][57]. Similarly, a negative influence of sarcopenia as measured by PMI and SMI on OS was found in patients undergoing trans-arterial chemo-embolization (TACE) and trans-arterial embolization (TAE) [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired nutritional status also frequently occurs in cirrhotic HCC patients. Despite some negative studies [8,9], most available data suggest that impaired nutritional status is also associated with unfavorable outcome in patients with HCC in general [10][11][12][13][14][15][16][17][18] as well as after tumor-specific treatment, such as liver resection [19][20][21][22], radiofrequency ablation [23,24], sorafenib [25,26], Lenvatinib [27], embolization [28] or radiotherapy [29]. Many new therapeutic modalities have recently been introduced for HCC, but prognosis remains poor.…”
Section: Introductionmentioning
confidence: 99%